Novel compound heterozygous mutations in LMAN2L cause early childhood refractory epilepsy - Teng Wang; Yan Gao; Yuhan Yan; Ping Yin; Lili Tong; Meng Dong (Italian Journal of Pediatrics)
Abstract Background Autosomal recessive mental retardation-52(MRT52) is a subtype of mental retardation whose clinical features include global developmental delay, severe intellectual disability with poor speech, and mild seizures in early childhood. Mutations in the LMAN2L gene resulting in mental retardation and seizures have been previously reported in 3 families. Here we describe 2 children in 1 family who presented with severe intellectual disability and drug-refractory epilepsy( DRE) at 2 months of age. Methods Two individuals from 1 family admitted to the pediatric department of Qilu Hospital were included in the study. Whole exome sequencing (WES) was used to detect LMAN2L gene variants. The clinical manifestations, electroencephalography, neuroimaging characteristics and treatment of epilepsy were retrospectively analyzed. Result We identified two new LMAN2L compound heterozygous variants, c.476A > G, p.D159G, c.1060_1061del, p.S354Pfs*29, which appeared in two children from the same family. Both cases showed severe postnatal psychomotor developmental lag and developed seizures at 2 months of age, which manifested themselves in a variety of ways and were not relieved by the administration of multiple antiepileptic drugs. Conclusion Complex heterozygous mutations at the newly identified locus of LMAN2L cause refractory epilepsy, with epileptic symptoms beginning at 2 months of age and manifesting as multiple seizure types and developmental delays. This is the first report to link LMAN2L to the phenotype of epileptic encephalopathy and refractory epilepsy, suggesting that the heterozygous p.D159G, p.S354Pfs*29 LMAN2L variants are likely pathogenic. These 2 newly identified pathogenic variants enrich the spectrum of pathogenic variants in the LMAN2L gene.